Specialty natural rubber latex and latex foam products made therefrom - Ramli, Roslim (2023)
Specialty natural rubber (SpNR) latex is a modified form of natural rubber (NR) latex, a colloidal natural polymer harvested from rubber trees known as Hevea brasiliensis. To date, there is limited information on the use of SpNR latex in latex foam products, possibly due to low total solid content (TSC), of which, for the production of latex foam products, the minimum TSC of the latex should be at least 60 %. In this study, a new generation of SpNR latex has been developed. Unlike the traditional method, which requires a processed latex known as low-ammonia NR (LATZ) latex as the starting material, SpNR latex in this study is produced directly from freshly tapped NR latex. Two varieties of SpNR latex: deproteinized natural rubber (DPNR) latex and epoxidized natural rubber (ENR) latex were produced. DPNR latex is prepared via a heat enzymatic hydrolysis process, whilst ENR latex is prepared via an in-situ epoxidation chemical modification process. Afterward, both DPNR and ENR latex were concentrated to a TSC of 60% via ultrafiltration process using membrane separation technology. The physicochemical properties of the SpNR latex were determined, and found to be slightly different to the commercial LATZ latex. Nevertheless, the availability of SpNR latex at 60% TSC, allows SpNR latex to be used to produce latex foam. In this study, the foamability and subsequent stability of the SpNR latex were evaluated, and hence the compounding, foaming, and gelling formulations to produce latex foam were developed. Additionally, this study found that DPNR latex can be used to produce latex foams in the three intended densities of high, medium, and low-density. However, for ENR latex, only high- and medium-density latex foams have been successfully produced. The lower the density the softer the material. Therefore, these findings suggest that DPNR latex foam is a better choice compared to ENR latex foam for certain latex foam products, especially when the latex foam products require light-weight and soft properties.